STRATEGI PENYULUH AGAMA DALAM PEMBERDAYAAN MUALLAF TURI KABUPATEN SLEMAN - Rosidin Rosidin; Widodo Widodo; Siti Aminah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2020)
Religious educators has prominent roles on community spiritual development, includes Muslim converts or Mualaf. Converts needs much more guidance to strengthen their faith. Therefore, religious educators should apply appropriate strategies to develop communities in both material and spiritual aspects. This paper tried to explain the strategies were used by religious educators to carry out their functions and the efforts to develop converts in Turi Subdisrict. This study applied qualitative approach. The results of the study were: first, religious educators have already properly conducted their function, includes: informative, educative, consultative, and advocative. Second, Convert empowerment program includes several activities, such as: Convert friendship forum; Faith strengthening and sharia practices; and convert’s economic development. Third, Religious educators roled as a bridge between converts and external parties, Regional Amil Zakat Agency (Bazda) of Sleman District and National Amil Zakat (Baznas), Religious Ministry, Religious Community Organization of Sleman District, Pokjaluh, and Regional Government of Sleman District.